THE INFLUENCE OF INFLATION RATE, SBI INTEREST RATE, EARNING PER SHARE, RUPIAH EXCHANGE RATE AND COMPANY FUNDAMENTALS ON STOCK PRICES IN TELECOMMUNICATION COMPANIES THAT GO PUBLIC FOR THE 2020-2023 PERIOD - Lestari , Safira Dwi; Utomo, Prasetyo; Ramdani, Rahmad; Hariyanto, Wiwit (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to analyze the impact of inflation rate, SBI interest rate, earnings per share (EPS), Rupiah exchange rate, and company fundamentals on stock prices in publicly listed telecommunication companies during the 2020-2023 period. Methods: A quantitative approach was employed using secondary data from 16 telecommunication companies selected through purposive sampling. Data were analyzed using descriptive statistics, classical assumption tests, and multiple regression analysis via SPSS version 27. Results: The findings reveal that all examined factors significantly influence stock prices. Inflation rate, SBI interest rate, EPS, Rupiah exchange rate, and company fundamentals collectively account for 82.3% of the variance in stock prices. Novelty: Unlike prior studies, this research focuses on telecommunication companies—a sector experiencing substantial growth during the COVID-19 pandemic due to increased digital connectivity demands. The study provides fresh insights by contextualizing macroeconomic and company-specific factors in a sector critical to economic recovery and resilience during crises. This comprehensive examination supports investors and policymakers in making informed decisions regarding stock investments in volatile market conditions.